2004
DOI: 10.1111/j.1472-765x.2004.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural community structure of cyanobacteria in the South China Sea as revealed by rpoC1 gene sequence analysis

Abstract: This is the first report about the cyanobacterial community structure in the South China Sea, and an important supplement to the current understanding of the relationship between genetic and ecological diversity and environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…Phylogenetic diversity amongst the 2 genera obtained from our study was similar to a previous report from the SCS based on rpoC1 gene sequences, which showed that picocyanobacteria in both surface waters and at 80 m depth were composed of HL II Prochlorococcus and clade II Synechococcus (Ma et al 2004). However, the considerable phylogenetic diversity within the 2 predominant clades, HL II Prochlorococcus and clade II Synechococcus, was augmented by the presence of HL I and LL IV Prochlorococcus genotypes and Synechococcus clades III, XV and XVI genotypes.…”
Section: Phylogeny and Distribution Of Picocyanobacteriasupporting
confidence: 89%
“…Phylogenetic diversity amongst the 2 genera obtained from our study was similar to a previous report from the SCS based on rpoC1 gene sequences, which showed that picocyanobacteria in both surface waters and at 80 m depth were composed of HL II Prochlorococcus and clade II Synechococcus (Ma et al 2004). However, the considerable phylogenetic diversity within the 2 predominant clades, HL II Prochlorococcus and clade II Synechococcus, was augmented by the presence of HL I and LL IV Prochlorococcus genotypes and Synechococcus clades III, XV and XVI genotypes.…”
Section: Phylogeny and Distribution Of Picocyanobacteriasupporting
confidence: 89%
“…Currently, the anthropogenically derived increase in atmospheric CO 2 is a global challenge which will change seawater chemical characteristics and particle-size distributions, as well as microbial function and diversity (13,15,30). With elevated partial CO 2 pressure (pCO 2 ), both primary production and the release of DOC might increase.…”
Section: Vol 77 2011mentioning
confidence: 99%
“…Furthermore, these clades have been repeatedly observed to coexist in a single water column (7,8,21,22,30,35,44). Synechococcus inhabits the world's coastal and oligotrophic oceans at high concentrations (typically 1 汐 10 3 to 1 汐 10 4 cells ml 溪1 ), and in the oligotrophic Atlantic, it comprises a significant portion of phytoplankton carbon (13), accounting for up to a quarter of primary production (29).…”
mentioning
confidence: 99%